Adiponectin and Interleukin-6, but not Adipose Tissue, are Associated with Worse Neurocognitive Function in HIV-Infected Men. Issue 2 (February 2015) - Lake, Jordan E; Vo, Quynh T; Jacobson, Lisa P; Sacktor, Ned; Miller, Eric N; Post, Wendy S; Becker, James T; Palella, Frank J; Ragin, Ann; Martin, Eileen; Munro, Cynthia A; Brown, Todd T
Background: Generalized obesity has been associated with cognitive decline, a process potentially mediated by adipocytokines. The effects of regional adipose tissue (AT) on cognition, however, are not well understood. We explored cross-sectional relationships between regional AT, adipocytokines, inflammatory markers and neuropsychological (NP) test scores among HIV+ and HIV- men enrolled in the Multicenter AIDS Cohort Study. Methods: Visceral, subcutaneous abdominal and subcutaneous thigh AT areas were quantified by computed tomography (CT). NP tests (Trail Making Test parts A and B, and Symbol-Digit Modalities) obtained within 2 years of CT screened for psychomotor speed and executive function. Adiponectin, leptin, interleukin-6 (IL-6) and high-sensitivity C-reactive protein (hs-CRP) were measured. Results: Of 509 HIV+ and 271 HIV- participants, HIV+ men (98% on antiretroviral therapy, 81% HIV-1 RNA<50 copies/ml) had lower median subcutaneous AT and adiponectin levels and higher hs-CRP levels, but visceral AT, body mass index, IL-6 and NP scores did not vary by HIV serostatus. In multivariable analysis, older age, ≤high school education and African American race, but not AT area or site, were associated with worse NP test scores among all participants. In HIV+ only, higher adiponectin and IL-6 were associated with worse cognitive function independent of AT area. No HIV-specific factors were associated with NP test scores. Conclusions: Demographic factors were associated with NP test performance, but regional adiposity was not. In HIV+ only, higher adiponectin and IL-6 were associated with worse NP test scores, supporting a role for chronic inflammation and adipocytokine imbalance in neurocognitive decline in HIV+ persons.